Trust in the banking sector in Poland in comparison to global trends - Dariusz Piotrowski (Ekonomia i Prawo, 2020)
Motivation: Banks are called public trust institutions. This term underlines the importance of trust in the activities of these institutions. The global financial crisis has drastically reduced public trust in banks. However, nowadays, at a time of a global crisis of social trust in broadly understood institutions, more and more people tend to trust banks. This phenomenon has given rise to the need to identify factors for restoring trust in banks. Aim: The aim of the study is to compare changes in the level of trust in banks in Poland with the trends observed in this respect on a global scale. Factors strengthening or weakening public trust in banks will be also identified. Results: The research shows that in the case of the Polish market, financial stability, improvement of the quality of services provided, and care for security are the factors that have been mainly responsible for the increase in trust in banks in recent years. On a global scale, efficient problem-solving/complaint handling is also an important determinant of high trust in banks. Moreover, cultural factors were identified as determinants of differences in the level of trust in the banking sector in countries of the Western and Eastern civilisations. The research also resulted in demonstrating that the changes in the level of trust recorded for the Polish market were to a large extent a reflection of processes taking place on a global scale. However, a more detailed analysis of the data showed that in the time of the financial crisis in 2009, the decline in the level of trust in banks observed in Poland was stronger than on the global market. In turn, during the period of global economy growth, one year before the outbreak of the COVID–19 pandemic, trust in the banking sector in Poland was at a higher level than the average level of trust in banks recorded on a global scale. Such a considerable dispersion of results stems mainly from factors of an emotional nature.